Playful Materialities The Stuff That Games Are Made Of - Beil, Benjamin; Freyermuth, Gundolf S.; Schmidt, Hanns Christian; Rusch, Raven (Bild und Bit. Studien zur digitalen Medienkultur, 2022)
Game culture and material culture have always been closely linked. Analog forms of rule-based play (ludus) would hardly be conceivable without dice, cards, and game boards. In the act of free play (paidia), children as well as adults transform simple objects into multifaceted toys in an almost magical way. Even digital play is suffused with material culture: Games are not only mediated by technical interfaces, which we access via hardware and tangible peripherals. They are also subject to material hybridization, paratextual framing, and processes of de-, and re-materialization.